Upaya Peningkatan Pengetahuan Masyarakat tentang Pencegahan Stunting melalui Pendidikan Komunitas Interaktif - Eko Fuji Ariyanto; Bianda Putri Ramadhani; David Firmansyah; Rizkiani Tri Ramdani; Muhammad Abian; Lauditta Nurseptia Prihandhini; Anisha Salmah Azhar; Fahmi Zacki Mubarak; Dwi Wahyudha Wira; Rima Destya Triatin (Universitas Mathla'ul Anwar Banten, 2019)
EFFORTS TO IMPROVE COMMUNITY KNOWLEDGE ABOUT STUNTING PREVENTION THROUGH EDUCATION OF INTERACTIVE COMMUNITIES. Stunting is one of the main health problems in Indonesia, including West Java Province. Some factors can cause this problem, especially inadequate nutrition. Community education regarding stunting prevention were delivered through interactive health promotion in Sayang village, Jatinangor sub-district, Sumedang district, West Java. The audiences were purposively selected, including village cadres and mothers with under-five children. The materials delivered in this program included practical information about how to prepare balanced nutrition for babies and under-five children. Seventy two audiences actively participated in this program. The enthusiasm of the audiences was very high, shown by very interactive discussion during this program. The participants could answer most of the questions given by the speakers. Community education through interactive health promotion which involved cadres and purposively selected group as the audiences was a reliable method to increase knowledge and awareness of the community for stunting prevention.